A new fixation method for anterior cruciate ligament femoral avulsion fracture: a rare case report and literature review - Shen, Jiquan; Hong, Liang; Zhou, Changjian; Wang, Xinggao; Ye, Zhijun; Wang, Bo (Frontiers in Surgery, 2025)
PurposeTo address the clinical challenges of femoral avulsion fractures of the anterior cruciate ligament (ACL), which are rare and lack a consensus on optimal treatment, through the presentation of a novel minimally invasive arthroscopic technique.MethodsAn 18-year-old female with an ACL femoral avulsion fracture and a medial collateral ligament (MCL) rupture underwent arthroscopic anchor stitching using a composite absorbable bone anchor. This technique aimed to achieve anatomical reduction and support early functional recovery.ResultsThe surgical intervention achieved successful anatomical reduction. At the 6-month follow-up, the patient exhibited full knee mobility, joint stability, and resumed normal activities without discomfort. By the final 17-month follow-up, computed tomography (CT) confirmed complete fracture union, with preserved joint architecture and no degenerative changes. The knee remained stable and pain-free, demonstrating sustained efficacy of the technique.ConclusionThe arthroscopic anchor stitching technique is a viable, minimally invasive option for ACL femoral avulsion fractures, promoting rapid recovery and excellent long-term outcomes. This case highlights the importance of early recognition and anatomical fixation for such injuries.